ANALISIS FLYPAPER EFFECT PADA PAD DAN DAU TERHADAP BELANJA DAERAH KABUPATEN/KOTA DI KIB DAN KIT - Putu Mahardika Adi Saputra; Trisyanti, Dela Irbah (Contemporary Studies in Economic, Finance and Banking, 2022)
This study aims to determine whether there is the flypaper in the western region of Indonesia and eastern region of Indonesia. This study uses a quantitative approach with Fixed effect model (FEM) as its method. This study uses secondary data that obtained through DJPK Ministry of Finance’s website to get Local Own-source Revenue (LOR), General Allocation Fund (GAF), Regional Expenditure and Central Bureau of Statistics to get population that used as control variable during the 2010-2020 period. The result of this study indicate that LOR, GAF, and population has a positive effects on regional expenditures. The flypaper effect also occurs in the western region of Indonesia and eastern region of Indonesia